(untitled) (Kronika Bydgoska, 2013)
The article presents the activity of the PTTK Voivodeship Board in Bydgoszcz in the years 1975-1990. The Voivodeship Board, consistent with the statute binding at that time, was an intermediate cell between the society’s head office and branches focusing their activity in an area in Poland specified by the statute. It also represented these branches before voivodeship authorities and was a co-ordinating body supervising them in the statutory-program scope on the regional scale. Political, social and economic transformations in the late 1980’s and the early 1990’s forced also making important transformations and modernisation of the society’s activity, especially in connection with coming into force of the law on associations, in the economic aspect. The new statute passed during the 12th PTTK National Congress on June 16, 1990 did not take into consideration the existence of voivodeship boards. This article presents the board’s organisational and program activity, the society’s organisational structures in the region, and describes the tourist base in the voivodeship, co-operation with local authorities, activity with school youth and in academic, handicraft and military communities, in the scope of guidance and foreign tourism.